2018
DOI: 10.15282/mohe.v7i2.203
|View full text |Cite
|
Sign up to set email alerts
|

Spiritual intelligence on health behaviours among Malaysian university students in a Malaysian public university: The mediating role of self efficacy

Abstract: University students experience a substantial amount of change where they progress from the highly controlled setting of school to the self-motivated environment of the university. Many changes which involve social, financial, and environment elements, can be a burden to the students putting them at risk in negative health behaviours. Negative health behaviours among university students are a course of concern since they have a tendency to be carried into adulthood which can possibly cause the emergence of chro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 21 publications
1
3
0
Order By: Relevance
“…The current results also confirm that SQ is positive and significantly influences the ESQ. The finding is consistent with previous researches [20], [21], [23], [48] emphasizing the critical nature of SQ's role in organizations for high performance at the workplace. It is due to how SQ develops an employee with selfawareness, behavior, the judgement of self-control, decision power, flexibility, adaptability, vision, consciousness, value, sense and intuition [50].…”
Section: Hypotheses Testingsupporting
confidence: 93%
See 2 more Smart Citations
“…The current results also confirm that SQ is positive and significantly influences the ESQ. The finding is consistent with previous researches [20], [21], [23], [48] emphasizing the critical nature of SQ's role in organizations for high performance at the workplace. It is due to how SQ develops an employee with selfawareness, behavior, the judgement of self-control, decision power, flexibility, adaptability, vision, consciousness, value, sense and intuition [50].…”
Section: Hypotheses Testingsupporting
confidence: 93%
“…These measures are intended to increase lecturers' satisfaction and enjoyment of their daily work. An academic working environment that is instilled with spiritual values such as respect, honesty, and connectedness will bring a positive impact to the learning experience [21], [26], [27], [30], [32]. Moreover, they all agree that SQ has a positive influence on a student's academic achievement, where it is posited that students can solve their problems wisely and make better solutions for themselves [28], [29].…”
Section: Hypotheses Testingmentioning
confidence: 99%
See 1 more Smart Citation
“…Individuals with a strong connection to their life purpose and spiritual values tend to be more passionate and diligent in achieving their financial goals. Dev et al, (2018) suggested that Spiritual intelligence focuses on self-awareness and reflection, which includes an understanding of life purpose, values and outlook. With a higher level of selfawareness, individuals will be more likely to plan and manage their personal finances wisely, allocating funds in accordance with greater goals and values.…”
Section: The Effect Of Spiritual Intelligence On Employee Personal Fi...mentioning
confidence: 99%